LncRNA Sox2ot modulates the progression of thoracic aortic aneurysm by regulating miR-330-5p/Myh11. Issue 7 (15th July 2020) - Xiao, Weizhang; Li, Xing; Ji, Cheng; Shi, Jiahai; Pan, Youmin
Abstract: Thoracic aortic aneurysm (TAA) has been causing the death of elder people. Myosin heavy chain 11 (Myh11) has been reported associated with aortic aneurysm, but there is no specific study on its function on TAA. Here we aimed to explore the function of Myh11 on mouse aortic smooth muscle cells (SMCs) for studying the inner mechanism of TAA. H2 O2 treatment was implemented on mouse aortic SMCs for detecting cell apoptosis. Meanwhile, functional assays were conducted to verify the function of Myh11 on mouse aortic SMCs. Also, pull-down assay, RIP assay were implemented to identify the potential RNAs for study. Quantitative real-time polymerase chain reaction (qRT-PCR) and luciferase reporter assay were implemented to identify the expression and binding relationships of RNAs. Myh11 expression was increased by treatment of H2 O2 . Myh11 could decrease proliferation and enhance apoptosis of mouse aortic SMCs. At the same time, mmu-miR-330-5p could bind to Myh11 and Sox2ot, forming a competing endogenous RNA (ceRNA) pathway to regulate the proliferation and apoptosis of mouse aortic SMCs. Moreover, both Sox2ot and Myh11 were proved to be up-regulated whereas miR-330-5p down-regulated in Fbn1 C1039G/+ mice, the in vivo model of TAA. In a word, long noncoding RNA (lncRNA) Sox2ot modulates the progression of TAA by regulating miR-330-5p/Myh11 axis.